Filhos da guerra, cainismo e protagonismo infanto-juvenil em Los Abel (1948), de Ana María Matute e Duelo en El Paraíso (1955), de Juan Goytisolo - Rossi, Cristiane Aparecida da Rosa (2018)
Cainism, a subject regularly approached in works belonging to the Spanish and Universal Literature, has as an initial presupposition, a report of chapter IV of the book of Genesis, since, by analyzing the mentioned term it is possible to understand it inserted in the contexts of the novels Los Abel (1948), by Ana Maria Matute (1925-2014) and Duelo en El Paraíso (1955), by Juan Goytisolo (1931-2017). This model of representation refers to the context in which the armed confrontation developed, called the Spanish Civil War (1936-1939), in which the population of Spain was split into two rival halves, the nationalists and republicans, leading us to believe that the authors of these worksused the biblical theme addressed in the plot of both, representing the social confrontation manifested in the armed struggle. In this, the immediate non-acceptance of change from one regime to another, that is, from monarchy to republic, would threaten the traditional structures of Spain, as well as the study of children‘s and adolescents‘ protagonism, evidenced in the novels mentioned above, constitutes one of the basic themes for the development of the present thesis, which has the aim of establishing a relation between cainism and children's and adolescents' protagonism, in these works, considering the preponderance of social events that impact the isolated individual. The protagonism of children and adolescents' revealed through ideological confrontations, as well as the absence of a representative, impel the individuals to take position in favor of one of the sides, highlighting that neutrality, in the case of adults, would imply acceptance of the conditions imposed by the winning group. On the other hand, in the case of young people as well as minors, in an or pursuit of a medium in which they could insert and maintain themselves. We highlight as a research question for this thesis, the power of social transformation played by the protagonism of children and youth, characterized in narratives, with respect to the modification of expectations produced within the social contexts in which they developed. As a specific goal, we will reflect on the influence of the historical memory of those who have witnessed war with a repercussion on Literature, thus defining it as a specific objective of the present study, given that the memory obliterated by the Franco regime continues to be recovered constantly as a consequence of the repression established by the social violence, defining, therefore, the study of the plots, of the themes cainism and children's and adolescents' protagonism, as well as of the contexts in which the works were produced, as the chosen methodology. The methodological course also includes the bibliographic review of authors such as Pedraza Jiménez and Rodrigues Cáceres (2012), Ramoneda (1998), Graham (2013), Buades (2013), Paz (2009) and others. The analysis of the actions, carried out by the central characters of the referred novels, will constitute the main elements that characterize of the social havoc originated by the war. The results emphasize the function of the literary text, understanding as one of the activating sources of the cognitive recovery mechanisms of memory.